Cold‐water or partial‐body cryotherapy? Comparison of physiological responses and recovery following muscle damage. (13th December 2017) - Hohenauer, E.; Costello, J. T.; Stoop, R.; Küng, U. M.; Clarys, P.; Deliens, T.; Clijsen, R.
Abstract : The aim of this study is to compare (a) the physiological responses following cold‐water immersion (CWI) and partial‐body cryotherapy (PBC) and (b) the effects on recovery following a muscle‐damaging protocol (5 × 20 drop jumps). Nineteen healthy males were randomly allocated into either a CWI (10°C for 10 minutes; n = 9) or a PBC (−60°C for 30 seconds, −135°C for 2 minutes; n = 10) group. The physiological variables (thigh muscle oxygen saturation [SmO2 ], cutaneous vascular conductance [CVC], mean arterial pressure [MAP], and local skin temperature) were assessed immediately prior and up to 60 minutes post‐treatment (10‐minutes intervals). The recovery variables (thigh muscle swelling, maximum voluntary contraction [MVC] of the right knee extensors, vertical jump performance [VJP], and delayed onset of muscle soreness [DOMS]) were measured immediately prior and up to 72 hours post‐treatment (24‐hours intervals). Compared to PBC values, CVC (at 30 minutes), SmO2 (at 40 minutes), and lower extremity skin temperature (thigh/shin at 60 minutes) were significantly reduced in the CWI group after the treatment (all P < .05). Only lower extremity skin temperature was significantly reduced in the PBC group directly post‐treatment (all P < .05). MAP significantly increased in both groups after the treatments (both P < .05). DOMS did not differ between groups. MVC and VJP returned to baseline in both groups after 24 hours ( P > .05). CWI had a greater impact on the physiological response compared to PBC. However, both treatments resulted in similar recovery profiles during a 72‐hours follow‐up period.